Purity, Nationalism, and Whiteness: The Fracturing of Fundamentalist Evangelicalism. Issue 4 (February 2021) - Herrmann, Andrew F.
Fundamentalist evangelicalism is an intricate grand narrative based upon the interrelated concepts of end times' eschatology and purity. These two concepts created the conditions by which white evangelicals abandoned their traditional moral rhetoric and overwhelmingly helped elect Donald Trump. However, the eschatological and purity concepts have also created the conditions by which evangelicalism is fracturing along racial and gender lines. This article, written by a former evangelical fundamentalist, looks at the grand narrative and the ruptures occurring within the culture, including the #ChurchToo movement and the rise of the #Exvangelicals.